ASEAN Integration Process as a Model of Successful Regional Integration - Jatmika, Muhammad Indrawan (Global and Policy Journal of International Relations, 2023)
The aim of this study is to provide a comprehensive understanding of successful regional integration by looking at the ASEAN regional integration process as the main case study. Previous research has explained that successful regional integration is indicated by success in increasing economic levels, inter-state linkages that support the achievement of political stability, and cultural linkages that encourage the creation of a mutual identity. This paper seeks to describe how ASEAN's efforts to achieve regional integration success. The three interconnected causal factors of regional integration theory—increasing interdependence between states, organizational capacity for resolving disputes, the emergence of international legal systems, and the states' expectation that supranational rules will eventually supplant national regulatory systems—led to the formation and the development of ASEAN. ASEAN believes that by implementing the ASEAN Community, which is supported by the three pillars of the ASEAN Economic Community, ASEAN Political-Security Community, and ASEAN Socio-Cultural Community, they can achieve all forms of integration through the process, including the economic, political, and socio-cultural integration.DOI https://doi.org/10.33005/jgp.v11i02.3711